Changes in echogenicity in the fetal brain: a prevalence study in fetuses at risk for preterm delivery - Rosier‐van Dunné, F. M. F.; van Wezel‐Meijler, G.; Odendaal, H. J.; van Geijn, H. P.; de Vries, J. I. P. (Ultrasound in obstetrics & gynecology, 2007)
Objectives To study the incidence of echodensities in the periventricular white matter, ventricular system, basal ganglia and thalamus of the brain in fetuses at risk for preterm delivery. Methods This was a prospective study of 124 fetuses with a gestational age between 26 and 34 weeks in pregnancies affected by either pregnancy‐induced hypertensive disorders or preterm labor. Transvaginal ultrasound examination of the fetal brain in coronal and sagittal planes was performed weekly until delivery and the neonatal brain was examined within 24 h after delivery. Results In 66% of all fetuses, echodensities were found in one or more areas of the brain. They were present in the periventricular area in 52% of cases, the intraventricular area in 18% and in the basal ganglia and thalamus area in 28%. Changes in echogenicity were seen throughout the entire gestational‐age period studied. Of the periventricular echodensities that exceeded in echodensity that of the choroid plexus, at least 50% persisted after delivery; at least 38% of the intraventricular echodensities and at least 32% of the basal ganglia and thalamus echodensities persisted after delivery. Conclusions In high‐risk fetuses, echodensities are a frequent finding in several areas in the brain. How far these echodensities are related to future outcome of the infant needs to be investigated. Copyright © 2007 ISUOG. Published by John Wiley & Sons, Ltd.